Meu materialismo não me limita: candomblé e consciência política em Jubiabá de Jorge Amado - Cruz, Cristiano de Araújo (2011)
In this master's thesis we make use of Jorge Amado´s (1912-2001) Jubiabá (1935) novel as a possibility of empirical documentation for the historian interested in certain aspects of brazilian culture, especially as regards the afro-brazilian religions. We aim also as the author involved with throbbing political issues of that historic moment, he highlights in his literary production, sympathy by the communist party and the engagement in the class struggle, to bring the scene fictional tensions and latent conflict in bahian society the first decades of the 20TH Century. We are concerned with in perceiving the lineaments in relation to the universe of Candomblé and the positioning of the work in relation to the class struggle. It is a question of looking at how this writer moves the events of the universe of Candomblé and of the work recorded in his memory - most of the times by participant observation - for the pages of his novels. It was as analysis, an entire system of beliefs of the candomblé baiano, inside of a broader historical frame, of conflict between labor and capital